ChemInform Abstract: Palladium and TEMPO as Co‐Catalysts in a Desulfinative Homocoupling Reaction. Issue 8 (February 2015) - Ortgies, Dirk H.; Chen, Fei; Forgione, Pat
Abstract Two sets of reaction conditions for the oxidative dimerization of aryl sulfinates to symmetrical biaryls using PdCl2 JohnPhos as the catalyst are presented.